Solid-state battery composite negative electrode and preparation method thereof
By hot pressing the lithium metal substrate with the metal sheet on the solid-state battery, the composite negative electrode of the lithium alloy layer is formed, which solves the problems of large interface impedance and short cycle life caused by lithium dendrites, and achieves efficient electron transmission and long cycle life.
Patent Information
- Application Number
- CN202411809922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
AI Technical Summary
The metal lithium negative electrode of solid-state batteries has large interface impedance and short cycle life due to dendrites' growth, which limits its practical application.
The lithium metal substrate and metal sheet (such as indium, tin, zinc, and magnesium) are used for hot pressing to form a composite negative electrode modified by the lithium alloy layer, and the growth of lithium dendrites is inhibited through spontaneous alloying reaction.
It achieves good interface contact, fast electron transmission, inhibits lithium dendrites' growth, improves the cycle life of the battery, and simplifies the preparation process, which is suitable for large-scale applications.
Smart Images

Figure CN119480935A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a negative electrode material for a solid-state battery. Background Art
[0002] Solid-state batteries are at the forefront of research in the field of secondary batteries, with the characteristics of high safety and high specific energy. However, the metal lithium negative electrode used in solid-state batteries has problems such as large interfacial impedance and short cycle life caused by dendrite growth, which limits its practical application. Therefore, inhibiting the growth of dendrites of metal lithium negative electrodes is the key to promoting the practical application of solid-state batteries. In order to solve these problems, researchers have proposed two effective measures: one is to load metal lithium in a porous skeleton and use the porous skeleton to disperse the deposition of metal lithium to inhibit the growth of lithium dendrites, but this type of porous structure of lithium metal negative electrode is difficult to form a good interface contact with the solid electrolyte, so it is difficult to be used in solid-state batteries. The second is to surface treat commercial lithium sheets, such as the invention patent CN 118281162A, which modifies the lithium metal surface with a lithium salt and a lithium metal alloy composite protective film by a solution contact method to inhibit the growth of lithium dendrites. Similarly, the invention patent CN 113140812A prepares lithium metal modified with a composite protective layer by a solution immersion method to inhibit the growth of lithium dendrites. However, lithium salts modified on the surface of lithium metal are usually electronically insulating, so they easily cause increased electrode polarization and deteriorate electrochemical performance. Invention patent CN 110600677A suppresses lithium dendrite growth by coating gallium-indium-tin liquid alloy on the surface of lithium metal, but the multi-component liquid alloy spontaneously reacts with lithium to form multi-component lithium alloys (such as lithium gallium alloy, lithium indium alloy, lithium tin alloy, etc.) with a large number of different grain boundaries, resulting in poor interface contact and potential interface side reactions. In addition, liquid alloys usually require high temperatures (such as 400°C) to be prepared, which limits their large-scale application. Invention patent CN 111435728 B uses physical vapor deposition to prepare a metal protective layer to protect the lithium metal negative electrode. However, due to the extremely low evaporation rate of physical vapor deposition (0.001-0.05nm / s), the metal protective layer is usually nanoscale, which is not enough to suppress lithium dendrite growth for a long time. In addition, it is difficult to obtain large-scale applications due to the limited cavity of the physical vapor deposition equipment. Therefore, it is necessary to develop efficient modification methods to promote the large-scale application of metallic lithium anodes.
[0003] Patent publication number CN 113745470A discloses a solid-state lithium battery composite negative electrode and a preparation method and application thereof. The preparation method of the solid-state lithium battery composite negative electrode comprises the following steps: providing a metal powder dispersion, wherein the size of the macroscopic minimum structural unit of the metal powder in the metal powder dispersion is less than 100nm, and the melting point of the metal powder is less than 200°C; coating the metal powder dispersion on the surface of the solid electrolyte, and forming a metal coating after drying; placing a lithium metal sheet on the metal coating for hot pressing, wherein the hot pressing temperature is 130°C to 170°C, and the pressure is 0.5N / cm 2 ~10N / cm 2 The hot pressing time is 1min to 50min, so that the metal powder melts and reacts completely with lithium metal to form an alloy, thereby inhibiting the growth of lithium dendrites. However, nano-scale metal powders have a large specific surface area, which is prone to interfacial side reactions during long-term cycles, deteriorating the interface. Therefore, the results of the embodiments of this invention patent show that this type of negative electrode can only achieve 100 cycles. Summary of the invention
[0004] In response to the technical problems of large interface impedance and short cycle life of solid-state battery negative electrodes, the present invention proposes a solid-state battery composite negative electrode and a preparation method, which effectively solves the problems of severe interface side reactions and dendrite growth caused by the large specific surface area of traditional negative electrodes, and the solid-state battery composed of the negative electrodes exhibits a long cycle life.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A method for preparing a solid-state battery composite negative electrode comprises the steps of composite one or both sides of a lithium metal substrate with a metal sheet and then performing a hot pressing process to form a lithium metal substrate modified with a lithium alloy layer formed by contacting the lithium metal substrate and the metal sheet.
[0007] The metal sheet is any one of metal indium, tin, zinc and magnesium.
[0008] The thickness of the lithium metal substrate is 50-500 μm.
[0009] The thickness of the metal sheet is 0.3-10 μm.
[0010] The pressure of the hot pressing treatment is 0.3-1 MPa.
[0011] Preferably, the pressure of the hot pressing treatment is 0.5-0.7 MPa.
[0012] The pressing time is 60 to 600 seconds.
[0013] Preferably, the pressing time is 120 to 400 seconds.
[0014] The pressing temperature of the hot pressing treatment is 20-100°C.
[0015] Preferably, the pressing temperature of the hot pressing treatment is 40-70°C.
[0016] A solid-state battery composite negative electrode and the application of the preparation method, the solid-state battery composite negative electrode and the ternary nickel-cobalt-manganese positive electrode (LiNi x Co y Mn z O2, where x+y+z=1), lithium iron phosphate positive electrode (LiFePO4), lithium manganese oxide positive electrode (LiMn2O4), and lithium cobalt oxide positive electrode (LiCoO2) constitute a solid-state battery.
[0017] The beneficial effects of the present invention are as follows: good interface contact is achieved by adjusting the type of metal flakes and preparation parameters, and a lithium metal composite negative electrode modified with a lithium alloy layer is formed through a spontaneous alloying reaction. This composite negative electrode avoids the presence of an electronic insulating layer, can achieve rapid electron transmission and inhibit lithium dendrite growth, thereby improving the cycle life of the battery. In addition, this preparation method is simple, safe, easy to prepare and apply on a large scale, and is conducive to promoting the industrial application of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 Optical photographs of the lithium metal substrate (a) and the lithium-zinc alloy layer modified lithium metal composite negative electrode (b) in Example 1.
[0020] Figure 2 This is a schematic diagram of the structure of the lithium-zinc alloy layer modified lithium metal composite negative electrode in Example 1; in the figure, 1, lithium-zinc alloy layer; 2, lithium metal substrate. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] A solid-state battery composite negative electrode, having a structure such as Figure 2 As shown, it includes a lithium zinc alloy layer 1 and a lithium metal substrate 2. The preparation method includes the following steps: a lithium sheet ( Figure 1 (a)) and zinc metal sheet with a diameter of 16 mm and a thickness of 8 μm ( Figure 1 (b)) After alignment, the two electrodes were placed under a press and a lithium-zinc alloy layer-modified lithium metal composite negative electrode was prepared at a pressure of 0.5 MPa, a pressing time of 200 s, and a pressing temperature of 25°C.
[0024] Preparation of electrolyte membrane: Polyvinylidene fluoride (PVDF) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in dimethylformamide (DMF) solvent in a mass ratio of 3:1, then cast on a polytetrafluoroethylene plate, dried and peeled off to obtain an electrolyte membrane.
[0025] LiNi 0.6 Co 0.2 Mn 0.2 Preparation of O2 composite positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O2: lithium lanthanum zirconium oxide (LLZO): conductive carbon (SP): PVDF are uniformly mixed in an N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:0.5:0.5 to form a slurry, which is then coated on an aluminum foil surface and dried to prepare a composite positive electrode.
[0026] Battery assembly and testing: Electrolyte membrane and LiNi 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was cut into small discs with diameters of 16 mm and 12 mm respectively and assembled into a solid-state battery with a lithium-zinc alloy layer-modified lithium metal composite negative electrode. The charge and discharge tests were carried out at a 0.1C rate. The corresponding electrochemical properties are shown in Table 1.
[0027] Comparative Example 1
[0028] A lithium sheet with a diameter of 16 mm and a thickness of 400 μm was placed on the electrolyte membrane with a diameter of 16 mm and a LiNi 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was assembled into a solid-state battery and charged and discharged at a rate of 0.1C. The corresponding electrochemical performance is also shown in Table 1.
[0029] Comparative Example 2
[0030] Preparation of composite negative electrode: Nano zinc particles are uniformly dispersed in tetrahydrofuran solvent to form a 5% dispersion, which is then sprayed on the surface of a lithium sheet and dried to prepare a composite negative electrode.
[0031] Battery assembly and testing: The prepared composite negative electrode was combined with the electrolyte membrane with a diameter of 16 mm and the LiNi 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was assembled into a solid-state battery and charged and discharged at a rate of 0.1C. The corresponding electrochemical performance is also shown in Table 1.
[0032] Comparative Example 3
[0033] Preparation of composite negative electrode: Nano zinc particles are evenly dispersed in tetrahydrofuran solvent to form a 5% dispersion, which is then sprayed on the surface of the lithium sheet and dried to prepare a composite negative electrode. The composite negative electrode is placed under a press, and the pressed composite negative electrode is prepared at a pressure of 0.5 MPa, a pressing time of 200 s, and a pressing temperature of 25°C.
[0034] Battery assembly and testing: The pressed composite negative electrode was combined with the electrolyte membrane with a diameter of 16 mm and the LiNi 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was assembled into a solid-state battery and charged and discharged at a rate of 0.1C. The corresponding electrochemical performance is also shown in Table 1.
[0035] Comparative Example 4
[0036] Preparation of composite negative electrode: zinc chloride is dissolved in tetrahydrofuran solvent to prepare a 5% zinc chloride solution, and then the solution is sprayed on the surface of the lithium sheet to form a composite negative electrode.
[0037] Battery assembly and testing: The prepared composite negative electrode was combined with the electrolyte membrane with a diameter of 16 mm and the LiNi 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was assembled into a solid-state battery and charged and discharged at a rate of 0.1C. The corresponding electrochemical performance is also shown in Table 1.
[0038] Table 1 Electrochemical properties of solid-state batteries prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3
[0039]
[0040] The results show that the composite negative electrode prepared by pressing and compounding zinc metal flakes and lithium flakes has the best electrochemical performance. This is mainly because the zinc metal flakes and lithium flakes form a lithium alloy layer on the surface of the lithium flakes through a spontaneous alloying reaction during the pressing process. This lithium alloy layer is electronically conductive and does not have any electronic insulating layer, so it can achieve rapid electron transmission and inhibit the growth of lithium dendrites, and finally achieve high coulomb efficiency, high capacity and long cycle life. When the lithium flakes in Comparative Example 1 are not treated in any way, the solid-state battery presents the lowest first-cycle coulomb efficiency and specific capacity. This is mainly due to the serious interface side reactions of the lithium flakes during the charge and discharge process, which leads to a decrease in coulomb efficiency and capacity, and causes lithium dendrite growth during long-term cycles, and deteriorates the electrochemical performance. Therefore, the solid-state battery composed of lithium flakes can only cycle 171 times, and the specific capacity decays to less than 80%. When the lithium flakes in Comparative Example 2 are modified by nano-zinc surface, alloying reaction also occurs on their surface to form a lithium-zinc alloy layer, so their coulomb efficiency, capacity and cycle life are better than those of lithium flakes. However, this lithium-zinc alloy layer is formed by the spontaneous reaction of nano-zinc particles and lithium sheets, so it is loose and porous, and it is difficult to form a close contact with the solid electrolyte, resulting in limited improvement in electrochemical performance. When Comparative Example 3 is pressed by the composite negative electrode prepared in Comparative Example 2, its coulombic efficiency, first-cycle specific capacity and number of cycles are slightly improved. The main reason is that the lithium alloy formed by the spontaneous reaction of nano-zinc particles and lithium sheets is loose and porous, and it is more compact macroscopically after pressing. However, from a microscopic point of view, there are still gaps between particles, so the performance improvement after pressing is limited. When the surface of the lithium sheet in Comparative Example 4 is treated with zinc chloride solution to form a composite layer of lithium chloride and lithium-zinc alloy, the interface side reactions can be effectively reduced, so its performance is better than that of the lithium sheet. However, since lithium chloride is electronically insulating, it will reduce electron transmission, so its performance is inferior to the composite negative electrode prepared in Example 1.
[0041] Embodiment 2-6
[0042] A solid-state battery composite negative electrode, the preparation method comprising the following steps: aligning a lithium sheet with a diameter of 16 mm and thicknesses of 30, 50, 200, 500, and 800 μm with an indium metal sheet with a diameter of 16 mm and a thickness of 6 μm, and placing them under a press, and preparing different lithium-indium alloy layer-modified lithium metal composite negative electrodes at a pressure of 0.6 MPa, a pressing time of 150 s, and a pressing temperature of 25°C.
[0043] Battery assembly and testing: The prepared lithium metal composite negative electrode modified with different lithium indium alloy layers was combined with the electrolyte membrane with a diameter of 16 mm and the LiNi with a diameter of 12 mm prepared in Example 1. 0.6 Co 0.2 Mn 0.2The O2 composite positive electrode was assembled into a solid-state battery and charged and discharged at a rate of 0.1C. The corresponding electrochemical performance is shown in Table 2.
[0044] Table 2 Electrochemical performance of solid-state batteries made of composite negative electrodes made of lithium sheets of different thicknesses
[0045]
[0046] The results show that the solid-state battery has the best performance within the preferred range of lithium sheet thickness. When the lithium sheet is too thin, the soft lithium sheet is easily deformed, resulting in poor contact with the indium metal sheet and failure to form a dense lithium-indium alloy layer, resulting in poor electrochemical performance. When the lithium sheet is too thick, cracks are easily formed on the surface of the lithium sheet and the indium metal sheet is over-alloyed, which is easy to form dendrites during long cycles, deteriorating the electrochemical performance.
[0047] Embodiment 7-13
[0048] A solid-state battery composite negative electrode, the preparation method comprising the following steps: aligning a lithium sheet with a diameter of 16 mm and a thickness of 200 μm with an indium metal sheet with a diameter of 16 mm and thicknesses of 0.2, 0.3, 0.8, 3, 6, 10, and 20 μm, respectively, and placing them under a press, and preparing different lithium-indium alloy layer-modified lithium metal composite negative electrodes at a pressure of 0.6 MPa, a pressing time of 150 s, and a pressing temperature of 25°C.
[0049] Battery assembly and testing: The prepared lithium metal composite negative electrode modified with different lithium indium alloy layers was combined with the electrolyte membrane with a diameter of 16 mm and the LiNi with a diameter of 12 mm prepared in Example 1. 0.6 Co 0.2 Mn 0.2 The O2 composite positive electrode was assembled into a solid-state battery and the charge and discharge test was carried out at a rate of 0.1C. The corresponding electrochemical performance is shown in Table 3.
[0050] Table 3 Electrochemical performance of solid-state batteries with composite negative electrodes made of indium metal sheets of different thicknesses
[0051]
[0052] The results show that the performance of the solid-state battery is best within the preferred thickness range of the indium metal sheet. When the indium metal sheet is too thin, the lithium-indium alloy layer formed is too thin to suppress the interface side reaction, resulting in poor electrochemical performance. When the indium metal sheet is too thick, the indium metal sheet and the lithium sheet are not fully alloyed, so that the active lithium on the composite positive electrode is replaced by indium metal during the charge and discharge process of the solid-state battery, resulting in reduced coulombic efficiency, specific capacity and cycle life.
[0053] Examples 14-17
[0054] Preparation of composite negative electrode: Lithium sheets with a diameter of 16 mm and a thickness of 300 μm were aligned with metal indium sheets, metal tin sheets, metal zinc sheets, and metal magnesium sheets with a diameter of 16 mm and a thickness of 6 μm, and then placed under a press. Different alloy layer-modified lithium metal composite negative electrodes were prepared at a pressure of 0.5 MPa, a pressing time of 300 s, and a pressing temperature of 25°C.
[0055] Preparation of electrolyte membrane: Polyethylene oxide (PEO), LiTFSI, and lithium lanthanum zirconium titanium oxide (LLZTO) were dissolved in dimethylformamide (DMF) solvent in a mass ratio of 3:1:1, then cast on a polytetrafluoroethylene plate, dried and peeled off to obtain an electrolyte membrane.
[0056] Preparation of LiFePO4 composite positive electrode: LiFePO4:LLZTO:SP:PVDF were uniformly mixed in NMP solvent at a mass ratio of 8:1:0.5:0.5 to form a slurry, which was then coated on the surface of aluminum foil and dried to prepare a composite positive electrode.
[0057] Battery assembly and testing: The electrolyte membrane and LiFePO4 composite positive electrode were cut into small discs with diameters of 16 mm and 12 mm respectively and assembled into solid-state batteries with lithium metal composite negative electrodes modified with different alloy layers. The charge and discharge tests were carried out at a rate of 0.2C. The corresponding electrochemical properties are shown in Table 4.
[0058] Comparative Example 4
[0059] Preparation of composite negative electrode: A lithium sheet with a diameter of 16 mm and a thickness of 300 μm was aligned with a metal copper sheet with a diameter of 16 mm and a thickness of 6 μm and placed under a press to prepare a composite negative electrode at a pressure of 0.5 MPa, a pressing time of 300 s and a pressing temperature of 25°C.
[0060] Battery assembly and testing: The prepared composite negative electrode was assembled into a solid-state battery with the electrolyte membrane with a diameter of 16 mm and the LiFePO4 composite positive electrode with a diameter of 12 mm prepared in Example 4, and the charge and discharge test was carried out at a rate of 0.2C. The corresponding electrochemical properties are also shown in Table 4.
[0061] Table 4 Electrochemical performance of solid-state batteries with composite negative electrodes made of different metal sheets
[0062]
[0063] The results show that when the metal flakes are indium and tin, the electrochemical performance of the solid-state battery is the best, and when the metal flakes are zinc and magnesium, the electrochemical performance of the solid-state battery is second. However, when the metal flakes are copper, the solid-state battery exhibits extremely poor electrochemical performance, mainly because the metal copper cannot alloy with lithium, resulting in the deposition and dissolution of the active lithium in the composite positive electrode of the solid-state battery only on the surface of the metal copper flakes during the charge and discharge process. Once consumed, the active lithium cannot be replenished. When the metal flakes are indium, tin, zinc, and magnesium, once they come into contact with the lithium sheet, they will alloy to form alloy layers such as lithium-indium, lithium-tin, lithium-zinc, and lithium-magnesium, and the alloy layer can replenish the active lithium consumed in the composite positive electrode of the solid-state battery.
[0064] Examples 18-24
[0065] A solid-state battery composite negative electrode, the preparation method comprising the following steps: aligning a lithium sheet with a diameter of 16 mm and a thickness of 200 μm and a metal tin sheet with a diameter of 16 mm and a thickness of 5 μm, and placing them under a press, and preparing different composite negative electrodes at pressures of 0.1, 0.3, 0.5, 0.6, 0.7, 1, and 1.5 MPa, a pressing time of 180 s, and a pressing temperature of 45°C.
[0066] Preparation of LiCoO2 composite positive electrode: LiCoO2:LLZTO:SP:PVDF were uniformly mixed in NMP solvent at a mass ratio of 8:1:0.5:0.5 to form a slurry, which was then coated on the surface of aluminum foil and dried to prepare a composite positive electrode.
[0067] Battery assembly and testing: The electrolyte membrane and LiCoO2 composite positive electrode prepared in Example 4 were cut into small discs with diameters of 16 mm and 12 mm respectively and assembled into a solid-state battery with a composite negative electrode. The charge and discharge tests were carried out at a rate of 0.1C. The corresponding electrochemical properties are shown in Table 5.
[0068] Table 5 Electrochemical performance of solid-state batteries prepared with composite negative electrodes at different pressures
[0069]
[0070]
[0071] The results show that the performance of solid-state batteries is best within the preferred pressure range. When the pressure is too low, the metal tin sheet and the lithium sheet cannot form a good interface contact, resulting in incomplete alloying, causing the active lithium of the solid-state battery composite positive electrode to be consumed by the unalloyed metal tin, thereby reducing the coulombic efficiency, specific capacity and cycle life. When the pressure is too high, the metal tin sheet and the lithium sheet are prone to deformation, and cannot form a good interface contact, resulting in low coulombic efficiency, specific capacity and cycle life of the solid-state battery.
[0072] Examples 25-31
[0073] A solid-state battery composite negative electrode, the preparation method comprising the following steps: aligning a lithium sheet with a diameter of 16 mm and a thickness of 200 μm and a metal tin sheet with a diameter of 16 mm and a thickness of 5 μm, and placing them under a press, and preparing different composite negative electrodes at a pressure of 0.6 MPa, a pressing time of 20, 60, 120, 250, 400, 600, and 1200 s respectively, and a pressing temperature of 60°C.
[0074] Battery assembly and testing: The electrolyte membrane prepared in Example 4 and the LiCoO2 composite positive electrode prepared in Example 5 were cut into small discs with diameters of 16 mm and 12 mm, respectively, and assembled with the composite negative electrode into a solid-state battery. The charge and discharge tests were carried out at a rate of 0.1C. The corresponding electrochemical properties are shown in Table 5.
[0075] Table 6 Electrochemical performance of solid-state batteries prepared with composite negative electrodes at different pressures
[0076]
[0077] The results show that the performance of the solid-state battery is optimal within the preferred pressing time range. When the pressing time is too short, the metal tin sheet and the lithium sheet cannot reach sufficient alloying time, resulting in incomplete alloying, and ultimately the active lithium of the solid-state battery composite positive electrode is consumed by the unalloyed metal tin, thereby reducing the coulombic efficiency, specific capacity and cycle life. When the pressing time is too long, the lithium alloy layer and the cross-section of the lithium sheet are easily oxidized by air to form electron / ion insulating lithium oxide, which causes the solid-state battery interface contact to deteriorate, resulting in low coulombic efficiency, specific capacity and cycle life.
[0078] Examples 32-38
[0079] Preparation of composite negative electrode: A lithium sheet with a diameter of 16 mm and a thickness of 200 μm was aligned with a metal tin sheet with a diameter of 16 mm and a thickness of 5 μm and placed under a press. Different composite negative electrodes were prepared at a pressure of 0.6 MPa, a pressing time of 250 s, and pressing temperatures of 10, 20, 40, 55, 70, 100, and 130 °C.
[0080] Preparation of electrolyte membrane: Dioxolane (DOL), LiTFSI, lithium hexafluorophosphate (LiPF6), and lithium aluminum germanium phosphate (LAGP) are dispersed in a fluoroethylene carbonate (FEC) solvent in a mass ratio of 6:1:2:2, then cast on a polytetrafluoroethylene plate, dried and peeled off to obtain an electrolyte membrane.
[0081] Preparation of LiMn2O4 composite positive electrode: LiMn2O4: lithium aluminum germanium phosphate (LAGP): Ketjen black (KB): PVDF are uniformly mixed in NMP solvent at a mass ratio of 8:1:0.5:0.5 to form a slurry, which is then coated on the surface of aluminum foil and dried to prepare a composite positive electrode.
[0082] Battery assembly and testing: The prepared electrolyte membrane and LiMn2O4 composite positive electrode were cut into small discs with diameters of 16 mm and 12 mm respectively and assembled with the composite negative electrode into a solid-state battery. The charge and discharge tests were carried out at a rate of 0.1C. The corresponding electrochemical properties are shown in Table 7.
[0083] Table 7 Electrochemical performance of solid-state batteries with composite negative electrodes prepared at different pressing temperatures
[0084]
[0085] The results show that the performance of solid-state batteries is best within the preferred pressing temperature range. When the pressing temperature is too short, the alloying process between the lithium sheet and the metal tin sheet is relatively slow, resulting in incomplete alloying, which in turn causes the loss of active lithium in the composite positive electrode of the solid-state battery and reduces the electrochemical performance. When the pressing temperature is too high, the lithium alloy layer and the lithium sheet are highly active and are easily oxidized by air to form electron / ion insulating lithium oxide, thereby reducing the ion / electron transmission capacity and also reducing the electrochemical performance of the solid-state battery.
[0086] Embodiment 39
[0087] Preparation of double-sided alloyed composite negative electrode: A lithium sheet with a length of 54 mm, a width of 42 mm, and a thickness of 100 μm was aligned with two metal tin sheets of the same size and a thickness of 5 μm in a sandwich structure (metal tin sheet-lithium sheet-metal tin sheet) and placed under a press. A double-sided alloyed composite negative electrode was prepared at a pressure of 0.6 MPa, a pressing time of 250 s, and a pressing temperature of 55°C.
[0088] Battery assembly and testing: The electrolyte membrane prepared in Example 32 and the LiMn2O4 composite positive electrode prepared in Example 32 were cut into the same size as the double-sided alloyed composite negative electrode, and assembled into a soft-pack solid-state battery (composite positive electrode-electrolyte membrane-double-sided alloyed composite negative electrode-electrolyte membrane-composite positive electrode), and charge and discharge tests were carried out at a rate of 0.1C. The corresponding electrochemical properties are shown in Table 8.
[0089] Comparative Example 5
[0090] Preparation of pressed lithium sheet negative electrode: A lithium sheet with a length of 54 mm, a width of 42 mm, and a thickness of 100 μm was placed under a press, and a pressed lithium sheet negative electrode was prepared at a pressure of 0.6 MPa, a pressing time of 250 s, and a pressing temperature of 55°C.
[0091] Battery assembly and testing: The electrolyte membrane prepared in Example 32 and the LiMn2O4 composite positive electrode prepared in Example 32 were cut into the same size as the pressed lithium sheet negative electrode, and assembled into a soft-pack solid-state battery (composite positive electrode-electrolyte membrane-pressed lithium sheet negative electrode-electrolyte membrane-composite positive electrode), and charge and discharge tests were carried out at a rate of 0.1C. The corresponding electrochemical properties are shown in Table 8.
[0092] Table 8 Electrochemical performance of solid-state batteries composed of double-sided alloyed composite anodes
[0093]
[0094] The results show that the soft-pack solid-state battery composed of double-sided alloyed composite negative electrodes exhibits extremely high first-cycle coulombic efficiency, discharge capacity and long cycle life. This is mainly because the metal tin sheet and the lithium sheet form an electronically conductive lithium-tin alloy layer on both sides of the lithium sheet through a spontaneous alloying reaction during the pressing process, which can achieve rapid electron transfer and inhibit the growth of lithium dendrites. However, the lithium sheet negative electrode without alloying layer modification will inevitably cause interface side reactions, which will then deteriorate the interface and cause dendrite growth, resulting in low first-cycle coulombic efficiency, low first-cycle discharge capacity and short cycle life.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid-state battery composite negative electrode, characterized in that: The single side or both sides of the lithium metal substrate are compounded with the metal sheet and then subjected to hot pressing treatment to make the lithium metal substrate and the metal sheet contact to form a lithium metal substrate modified with a lithium alloy layer.
2. The method for preparing a solid-state battery composite negative electrode according to claim 1, characterized in that: The thickness of the lithium metal substrate is 50-500 μm.
3. The method for preparing a solid-state battery composite negative electrode according to claim 2, characterized in that: The metal sheet is any one of metal indium, tin, zinc and magnesium.
4. The method for preparing a solid-state battery composite negative electrode according to claim 3, characterized in that: The thickness of the metal sheet is 0.3-10 μm.
5. The method for preparing a solid-state battery composite negative electrode according to claim 4, characterized in that: The pressure of the hot pressing treatment is 0.3-1 MPa.
6. The method for preparing a solid-state battery composite negative electrode according to claim 5, characterized in that: The pressure of the hot pressing treatment is 0.5-0.7 MPa.
7. The method for preparing a solid-state battery composite negative electrode according to claim 6, characterized in that: The pressing time is 60 to 600 seconds.
8. The method for preparing a solid-state battery composite negative electrode according to claim 7, characterized in that: The pressing temperature of the hot pressing treatment is 20-100°C.
9. The method for preparing a solid-state battery composite negative electrode according to claim 8, characterized in that: The pressing temperature of the hot pressing treatment is 40-70°C.
10. A solid-state battery composite negative electrode prepared by the method described in any one of claims 1-9.
Citation Information
Patent Citations
Lithium metal anode, preparation method thereof and lithium metal, lithium-sulfur and lithium air batteries
CN110600677A
Lithium metal anode protective layer, its preparation method and application
CN111435728B
Lithium metal negative electrode, preparation method thereof and lithium secondary battery
CN113140812A
Solid-state lithium battery composite negative electrode, and preparation method and application thereof
CN113745470A
Lithium metal anode, method for manufacturing same, and lithium metal battery
CN118281162A